Revitalisasi Pendidikan Cinta Tanah Air di Pondok Pesantren Darul Ihsan Menganti Gresik - Muhamad Arif (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2018)
Education patriotism at Pondok Pesantren Menganti Gresik, especially Darul Ihsan Menganti has been very intense to be done. Pondok Pesantren Darul Ihsan Menganti covered education of Play Group, Madrasah Ibtidaiyah, Madrasah Tsanawiah, Madrasah Aliyah, Vocational High School and Islamic College of Al-Azhar. The aim of this resesarch was to know how the application of the education patriotism and its implications for the daily life of Santri. The research used qualitative methods. In collecting data the researhcer used observation, interview and documentation. The results showed that the application of education patriotism at Pondok Pesantren Darul Ihsan divided into categories, namely the application of formal and informal education. And there were ongoing implications for the santri's daily life such as mutual cooperation in positive terms and commemorating the national day Key words: Education Patriotism, Pondok Pesantren, Revitalization of Education Patriotism